Search for stealth supersymmetry in events with jets, either photons or leptons, and low missing transverse momentum in pp collisions at 8 TeV - (:unkn) unknown (ELSEVIER, 2015)
The results of a search for new physics in final states with jets, either photons or leptons, and low missing transverse momentum are reported. The study is based on a sample of proton-proton collisions collected at a center-of-mass energy root s = 8 TeV with the CMS detector in 2012. The integrated luminosity of the sample is 19.7 fb(-1). Many models of new physics predict the production of events with jets, electroweak gauge bosons, and little or no missing transverse momentum. Examples include stealth models of supersymmetry (SUSY), which predict a hidden sector at the electroweak energy scale in which SUSY is approximately conserved. The data are used to search for stealth SUSY signatures in final states with either two photons or an oppositely charged electron and muon. No excess is observed with respect to the standard model expectation, and the results are used to set limits on squark pair production in the stealth SUSY framework. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: CMS; Physics; Stealth; Supersymmetry; Photons; Leptons; Low missing transverse energy